Tecnologias assistivas no ensino de matemática para estudantes com Transtorno do Espectro Autista (TEA) nos anos iniciais do ensino fundamental - Lopes, Cjanna Vieira (2023)
This research has as its theme the Assistive Technologies (AT) used to teach Mathematics to students with Autism Spectrum Disorder (ASD), in the early years of Elementary School. The objective is to identify, describe and analyze the AT that can help in the teaching-learning process of Mathematics of students with ASD in this stage of education. In order to achieve this objective, a bibliographical research complemented with a documentary research was established, with emphasis on a literature review of the Meta-analysis type. The latter was carried out in the databases: Scientific Electronic Library Online (SciELO), Periodicals Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES), Digital Library of Theses and Dissertations (BDTD) and Google Scholar. A time frame from 2015 to 2022 was applied, with four items as inclusion criteria: a) Talk about ASD; b) Addresses the teaching-learning of Mathematics; c) Has delimited the initial years of Elementary School; d) Bring examples of Assistive Technologies. At the end, seven texts, 5 dissertations and 2 articles, were selected to compose the Meta-analysis. As a result, several types of Assistive Technologies were found, being classified as: Technological AT, Methodological AT and Pedagogical AT. In addition, a certain preponderance of games and Adapted Materials such as AT for teaching Mathematics was identified both within the regular classroom and in the Multifunctional Resource Rooms. It is concluded from this investigation that, regardless of the type of Assistive Technology that one chooses to use, one must first understand the educational needs of students with ASD and choose an AT that meets them, making the necessary adjustments.